163k views
4 votes
Choose True or False for each equation.

3 × ( 3 + 3 ) = 6 × 3
A True B False


2 × ( 3 + 3 ) = 2 × 5
A True B False


( 3 × 8 ) + ( 8 × 8 ) = 11 × 8
A True B False


( 1 × 2 ) + ( 4 × 1 ) = 4 × 3
A True B False

User Benoni
by
5.4k points

2 Answers

6 votes

Answer:

Explanation:

3*(3+3)=6*3

3*6=6*3 true

2*(3+3)=2*5

2*6=2*5

12=10 false

(3*8)+(8*8)=11*8

24+64=11*8

88=88 true

(1*2)+(4*1)=4*3

2+4=4*3

8=12 false

User Abel Callejo
by
5.9k points
2 votes

Explanation:

A=True

B=False

C=True

D=False

User Andrew Senner
by
5.4k points